Geneza ETA i jej działalność w okresie dyktatury generała Francisco Franco (1952–1973) - Łaciuk, Wiktoria (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
In this article, the author analyses the origins and first years of activity of the Basque terrorist group ETA. It includes both the evolution of ETA’s ideology and the most important examples of its armed struggle. In order to improve the understanding of the mechanisms behind the founding of this terrorist organization, the first part of the paper contains a brief history of Basque nationalism and an overview of the situation in the region during and soon-after the Spanish Civil War. The main part of the article traces the path the organization took, turning from a student association focused on preserving language and culture to a highly functioning terrorist group capable of carrying out the assassination of admiral Carrero Blanco – the then Prime Minister and dictator’s protégé
Keywords: ETA; terroryzm; Franco, Francisco (1892-1975)